Launching Phonon Polaritons by Natural Boron Nitride Wrinkles with Modifiable Dispersion by Dielectric Environments. Issue 38 (18th August 2017) - Duan, Jiahua; Chen, Runkun; Li, Jingcheng; Jin, Kuijuan; Sun, Zhigang; Chen, Jianing
Abstract : Interference‐free hyperbolic phonon polaritons (HPPs) excited by natural wrinkles in a hexagonal boron nitride (hBN) microcrystal are reported both experimentally and theoretically. Although their geometries are off‐resonant with the excitation wavelength, the wrinkles compensate for the large momentum mismatch between photon and phonon polariton, and launch the HPPs without interference. The spatial feature of wrinkles is about 200 nm, which is an order of magnitude smaller than resonant metal antennas at the same excitation wavelength. Compared with phonon polaritons launched by an atomic force microscopy tip, the phonon polaritons launched by wrinkles are interference‐free, independent of the launcher geometry, and exhibit a smaller damping rate (γ ≈ 0.028). On the same hBN microcrystal, in situ nanoinfrared imaging of HPPs launched by different mechanisms is performed. In addition, the dispersion of HPPs is modified by changing the dielectric environments of hBN crystals. The wavelength of HPPs is compressed twofold when the substrate is changed from SiO2 to gold. The findings provide insights into the intrinsic properties of hBN‐HPPs and demonstrate a new way to launch and control polaritons in van der Waals materials. Abstract : Hexagonal boron nitride is identified as a natural material supporting hyperbolic phonon polaritons (HPPs). In situ infrared nanoimages reveal that intrinsic wrinkles can launch interference‐free wavefronts of HPPs with low loss. It is both theoretically and experimentally verified that the dispersion of HPPs can be tuned through the surrounding dielectric environments.